THE CONCEPT OF YUGAYYIRUNNA KHALQALLĀH IN THE VIEW OF MUFASSIR - Charis Chasan Ubaidillah; Ahmad Nurrohim; Kyeyune Hamidu; Hamzah Assuudy Lubis (Universitas Muhammadiyah Surakarta, 2023)
The Qur'an is a revelation of Allah subhanahu wa ta'ala and the basis of Islam is a guide for humans for a good afterlife. The Qur'an is a treatise, a form of great gift that Allah subhanahu wa ta'ala bestows on humans towards virtue, goodness, avoiding misguidance, peace and being merciful and good news for people who surrender wholeheartedly to Allah subhanahu wa ta'ala (Qur'an 16:89). The Qur'an is a sacred book that was revealed as guidance based on knowledge and as proof of the truth (Qur'an 7:52). As evidence of the oneness of Allah subhanahu wa ta'ala in the Qur'an, there is a lot of knowledge based on the Qur'an such as the creation of man (Qur'an 23:12-14). Not only detailed in its creation, but Allah subhanahu wa ta'ala also states clearly, that humans are the best of creation (Qur'an 95: 4). Humans are special and perfect creatures, however, behind the perfection that humans have, Allah subhanahu wa ta'ala gives lust as a fitrah to be used as an impetus in human survival. Lust has a strong influence on humans, the more it intervenes in a pure heart, the easier it is to mix the heart with the impulse of lust that is worldly. The lust that tends to the physical encourages humans to get pleasure and enjoyment from lust. Examples such as pride, greed, arrogance, and ingratitude. It causes man to begin to change what Allah subhanahu wa ta'ala has given him. This article examines the thoughts of several mufasirs regarding Yugayyirunna Khalqallāh (changing Allah's creation). This study is library research with a qualitative approach. The data collection used is documentation. This study utilizes the works of 7 carefully selected mufasirs. The data is analyzed using the contents analysis method. The study found that Yugayyirunna Khalqallāh is divided into several parts such as (i) physical and non-physical changes (ii) permissible and prohibited changes (iii) permanent and non-permanent changes (iv) the impact of Yugayyirunna Khalqallāh behaviour in the perspective of science.